Civilizational Analysis in Historical Sociology and Explanations of the “Soviet Collapse" - M. V. Maslovskiy (Социология власти)
The article deals with attempts to explain the collapse of the Soviet version of modernity — and the disintegration of the USSR — in (post)-Sovietology and historical sociology. It is argued that (post)-Sovietological studies were often characterized by a certain degree of ideological bias. In these studies, the example of “Soviet collapse” was generally used for a confirmation of earlier approaches to Soviet history. At the same time, they mostly focused on the immediate preconditions of that event rather than on long-term historical processes. The shortcomings of this approach can be overcome if we draw on historical sociology. The article considers the prediction of disintegration of the USSR offered by Randall Collins and Johann Arnason's analysis of the Soviet version of modernity. Both sociologists characterized the Soviet collapse in the context of long-term historical dynamics. While Collins's approach demonstrates a peculiar geopolitical determinism, Arnason singles out various factors of the dynamics of the alternative version of modernity. In the first half of the 1990s, Arnason applied his model of imperial modernization to the Soviet system, but later emphasized the civilizational aspects of communist modernity. This can also be seen in his evaluation of the Soviet collapse. In the literature on Soviet collapse, a contrast between the USSR and China is often highlighted, with structural and particularly economic factors being commonly highlighted. In contrast, the article argues that — for a comprehensive understanding of transformation processes in China — we need to consider the cultural sphere by drawing on sociological civilizational analysis.